Facilitating cardiopulmonary resuscitation training in high-risk areas of England: A study protocol - Hawkes, Claire A; Staniszewska, Sophie; Vlaev, Ivo; Perkins, Gavin D; Howe, Deska; Khalifa, Elyas; Mustafa, Yassar; Parsons, Nicholas; Lin, Yin-Ling; Rycroft-Malone, Jo (Resuscitation plus, 2023)
•First study exploring the topic in England.•Collaborative design with members of communities that are the subject of the study.•Will provide much needed evidence for stakeholders, and members of public. Bystanders’ interventions improve chances of survival from out-of-hospital cardiac arrest (OHCA) before Emergency Medical Services arrive. Some areas in England are of concern. These high-risk areas have a higher incidence of cardiac arrest combined with lower-than-average bystander CPR rates and are characterised by higher proportions of minority ethnic group residents and deprivation. Collaborating with people from the Black African and Caribbean and South Asian minority communities in deprived areas of England, we aim to develop and evaluate the implementation of theoretically informed intervention(s) to address factors contributing to lower bystander intervention rates. The study is a collaborative realist enquiry, informed by the Theoretical Domains Framework and associated Behaviour Change Wheel. It consists of 1) a realist evidence synthesis to produce initial program theories developed from primary workshop data and published evidence. It will include identifying factors contributing to the issue and potential interventions to address them; 2) theoretically informed intervention development, using the initial program theories and behaviour change theory and 3) a realist mixed methods implementation evaluation with embedded feasibility. Public involvement (PPI) as study team and public advisory group members is key to this study. We will conduct realist evidence synthesis, qualitative and statistical analyses appropriate to the various methods used. We will develop a dissemination plan and materials targeted to members of the public in high-risk areas as well as academic outputs. We will hold an event for participating community groups and stakeholders to share findings and seek advice on next steps. ISRCTN90350842. Registration date 28.03.2023. The study was registered after its start date.